The comparative morphometric analysis of seeds representatives of the genus Paeonia L. (PaeoniaceaeRudolphi) of the Kazakh Altai’s flora, introduced in the Altai Botanical Garden - Sumembayev, А.А.; Danilova, А.N. (Fundamental and Experimental Biology, 2021)
The article provides data on the study of the external structure, morphometric and weight parameters of seeds of the complex of Paeonia anomala L., P. hybridа Pall., P. intermedia C.A. Mey., grown in the conditions of the mountain-taiga zone of the Kazakhstan Altai, and clarification of the possibility of using these characters to distinguish between species. The primary analysis of the seed material revealed differences in the length, width and thickness of the seed in the cultivated samples from different ecological and geographical conditions of the habitats. A comparative study of such morphometric and weight parameters as the external structure, length, width, and thickness of seeds of the samples of Paeonia anomala, P. hybrida, P. intermedia, introduced from different ecological and geographical habitats of Kazakhstan Altai, revealed a certain variation in the selected parameters in the species. When comparing the external morphological structure of P. intermediaand P. anomala, the differences were practically not established, due to the close relationship of the species. When comparing the average metric and weight parameters of seeds in the Paeonia anomala specimens taken from ridge Ivanovsky, did not reveal significant differences. This happened despite the interpopulation difference in quality of the planting material with respect to ecology and location above sea level. This indicates the evenness of the length, width, and thickness of the seed material of the cultivated Paeonia anomala specimens. In cultivate specimens of P. hybrida from Narym ridge and Azutau in the ratio of the length, width and thickness of the seed, as well as the weight of 1000 pieces, seed differences were observed. Despite the low level of variability of morphological parameters of seeds, it is premature to recommend them for differentiation of species due to the short duration of the study period.